Wireless Portable Charger 3 in 1 / Nuramirah Ainaa Jamil - Jamil, Nuramirah Ainaa (2020)
We are from Gijutsu Tech Sdn. Bhd. have been in IT industry for a period of long time. The purpose of this report is to give the overview of our new product which is Wireless Portable Charger 3 in 1. The objective of our company is to produce stellar products, design and services that are suitable at a cost that represent the possible value to our customers. This new innovation is to overcome difficulties and help the students, business people and adult save their time during work, travel and can be use anytime without worrying where to charge or running out of batteries. We came up with a solution to design a charger with a few new and interesting features. The whole concept of this charger was to make their life easier. The concept of product is done by sketching.